Features of establishing legal facts in tax law enforcement - A. Krasyukov (Правоприменение, 2017)
УДК 347.73The subject. The article is devoted to the study of peculiarity of legal facts in tax law and law enforcement.The purpose. The article is aimed to identify key features of legal facts significant to law enforcement and to assess how knowledge of these features affects the law enforcement.Methodology. The author uses analysis of scientific sources as well as formally legal method and interpretation of legal norms and judicial acts.Results, scope of application. The author distinguishes specific features of legal facts in tax relations, which determine the specifics of their establishment. The presence of public will in the basis of the legal fact cannot be considered as it’s specific legal and tax feature, because any legal fact acquires their value only by will of the state. The author identifies the characteristics of the legal facts important for tax law enforcement: the complexity of the tax legal facts; "a fact-relationship" among the elements of the set of facts; legal facts (sets of facts) in large part are outside the regulation of the tax law; uncertainty of the entity, establishing the legal facts.Tax obligation arises from the existence of the economic relation, as a rule, in sphere of civil turnover. Transaction as a legal fact must be viewed as a legal act in relation to civil law, but transaction will be a legal deed in relation to the tax law. The transaction in relation to tax law can be called indirect legal fact.Transaction as a legal fact often has two aims: the aim of the first level is the entry into civil law relations to obtain material benefits, and the purpose of the second level is the entry into the tax-legal relationship for paying tax.In addition to the complexity of the tax legal facts law enforcement practice is difficult be-cause of large number of defective legal facts in tax relations. Defects of tax legal facts, the reasons for their occurrence and consequences for tax relations are analyzed. Formally, the defective legal facts give rise to legal consequences in tax relations.The various qualifications of tax legal facts by the taxpayer or the tax authority can be de-termined by using different evidence or by different valuation of the same evidence.Conclusions. Attention to peculiarities of tax legal facts is a prerequisite to the effective tax law enforcement in modern conditions.